2017
DOI: 10.1371/journal.pone.0179165
|View full text |Cite
|
Sign up to set email alerts
|

Detection of genome-edited mutant clones by a simple competition-based PCR method

Abstract: Genome editing by the CRISPR/Cas9 (clustered regularly interspaced short palindromic repeats / CRISPR-associated protein 9) system is a revolutionary strategy to study gene functions. Since the efficiency of gene disruption in cell culture does not reach 100% typically, cloning of mutant cells is often performed to obtain fully mutated cells. Therefore, a method to discriminate accurately mutated clones easily and quickly is crucial to accelerate the research using CRISPR/Cas9. Here, we show that knockout cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 21 publications
0
30
0
Order By: Relevance
“…There are two isoforms of sphingosine kinases in mammalian cells, sphingosine kinase 1 (SphK1) and sphingosine kinase 2 (SphK2), both of which are capable of phosphorylating sphingosine into S1P ( Maceyka et al, 2005 ). To investigate the role of SphKs, we employed the CRISPR/Cas9-based genome editing strategy to generate a control and the double kinase knock-out cell line based on HeLa MZ cells( Figure 4—figure supplement 1 ) ( Ran et al, 2013 ; Liao et al, 2015 ; Harayama and Riezman, 2017 ). After showing that removing sphingosine kinases did not disrupt mitochondria morphology or membrane potential ( Figure 4—figure supplement 2 ), we carried out uncaging experiments using Mito-So in the cell lines and measured their sphingolipid levels.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There are two isoforms of sphingosine kinases in mammalian cells, sphingosine kinase 1 (SphK1) and sphingosine kinase 2 (SphK2), both of which are capable of phosphorylating sphingosine into S1P ( Maceyka et al, 2005 ). To investigate the role of SphKs, we employed the CRISPR/Cas9-based genome editing strategy to generate a control and the double kinase knock-out cell line based on HeLa MZ cells( Figure 4—figure supplement 1 ) ( Ran et al, 2013 ; Liao et al, 2015 ; Harayama and Riezman, 2017 ). After showing that removing sphingosine kinases did not disrupt mitochondria morphology or membrane potential ( Figure 4—figure supplement 2 ), we carried out uncaging experiments using Mito-So in the cell lines and measured their sphingolipid levels.…”
Section: Resultsmentioning
confidence: 99%
“…Mutant cells were generated by the CRISPR/Cas9 system from Streptococcus pyogenes ( Ran et al, 2013 ), using the HPRT co-targeting strategy ( Liao et al, 2015 ) as previously described ( Harayama and Riezman, 2017 ). Target sequences (listed below) were selected based on high specificity and efficacy scores predicted by the CRISPOR algorithm ( Haeussler et al, 2016 ), and the corresponding pairs of oligo DNA were synthesized (Microsynth AG, Balgach, St. Gallen, Switzerland).…”
Section: Methodsmentioning
confidence: 99%
“…We demonstrated that genome-editing events at multiple loci can be detected in a single-tube endpoint ORNi-PCR (Fig. 7), which has not been achievable before using endpoint PCR-based methods 13 , 14 . In this regard, the primer combination should be more carefully considered to avoid overlap of amplicons in the endpoint PCR-based methods.…”
Section: Discussionmentioning
confidence: 93%
“…On the other hand, because ORNi-PCR generates positive PCR signals when one allele of the genome of a target cell is edited, it may be difficult to distinguish bi- and mono-allelic mutations by endpoint ORNi-PCR. This feature is one of the drawbacks of ORNi-PCR not found in endpoint PCR-based methods 13 , 14 (Table 1). Thus, endpoint ORNi-PCR should be primarily used to detect genome-edited cells possessing at least mono-allelic mutations at a target site before subsequent detection of mono- or bi-allelic mutations by other methods.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation